Peran Orang Tua Sebagai Murobbi Dalam Pembentukan Karakter Santri Di Masa Liburan - Nurjaman, Fauzi; Yuniarti, Yanti; Ardila, Yopi; Al Ishaq, Imam Abdimullah; Khoiriyah (Educational Research Center, 2026)
Parents' role as murobbi plays a strategic role in maintaining the continuity of character formation in students, particularly during vacations when students return to their families. Vacations are a critical period due to changes in the environment, routines, and supervision systems that can potentially weaken the internalization of character values ​​developed in Islamic boarding schools. This study aims to analyze the role of parents as murobbi, the parenting strategies implemented during vacations, and the supporting and inhibiting factors in character formation in students. This research used a qualitative approach with a case study conducted at Al-Kaaffah Islamic Boarding School, Kuningan, West Java. Data were collected through participant observation, semi-structured interviews, and documentation studies with informants including parents, boarding school administrators, and students. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing, using triangulation techniques to maintain data validity. The research findings indicate that parents who actively fulfill the role of murobbi (leaders) are able to maintain the continuity of their students' character through role models, religious supervision, instilling discipline, and ongoing educational communication. However, variations in parental commitment and readiness are inhibiting factors in the sustainability of character development. This research emphasizes the importance of strengthening synergy between Islamic boarding schools and families in maintaining the ongoing character education of students.